2011
DOI: 10.1111/j.1471-4159.2011.07176.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional importance of inositol‐1,4,5‐triphosphate‐induced intracellular Ca2+ mobilization in galanin‐induced microglial migration

Abstract: J. Neurochem. (2011) 117, 61–70. Abstract Galanin (GAL) is a neuropeptide which is up‐regulated following neuronal axotomy or inflammation. One subtype of GAL receptor (GalR2) is reported to be expressed in the brain’s immune cell population, microglia. In the present study, we investigated the effect of GAL on microglial migration and compared the mechanism with that of bradykinin (BK). GAL significantly increased the migration of rat cultured microglia at 0.1 pM. The GAL‐induced signal cascade was partly sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Endogenous GAL 2 -induced activation of the MAPK/ERK pathway via PKC has been reported in rodent hippocampal neurons (Hawes et al, 2006;Elliott-Hunt et al, 2007), rat microglial cells (Ifuku et al, 2011), rat PC12 pheochromocytoma cells (Hawes et al, 2006), and human small-cell lung cancer (SCLC) cells (Seufferlein and Rozengurt, 1996), although in the latter, MAPK/ ERK pathway activation can also occur independently of PKC (Wittau et al, 2000). GAL 2 predominantly couples to a G q/11 -type G protein, leading to phospholipase C activation, which stimulates Ca 2+ release via inositol phosphate hydrolysis and opens Ca 2+ -dependent ion channels in a PTXresistant manner, in both GAL 2 -transfected cell lines (Smith et al, 1997b;Borowsky et al, 1998;Fathi et al, 1998;Pang et al, 1998;Wang et al, 1998c) and GAL 2 -expressing rat microglial cells (Ifuku et al, 2011). GAL 2 activation led to a decrease in both Rho and Cdc42 GTPase activity and activation of cofilin in rat PC12 pheochromocytoma cells (Hobson et al, 2013).…”
Section: B Galanin Receptor Signalingmentioning
confidence: 97%
See 1 more Smart Citation
“…Endogenous GAL 2 -induced activation of the MAPK/ERK pathway via PKC has been reported in rodent hippocampal neurons (Hawes et al, 2006;Elliott-Hunt et al, 2007), rat microglial cells (Ifuku et al, 2011), rat PC12 pheochromocytoma cells (Hawes et al, 2006), and human small-cell lung cancer (SCLC) cells (Seufferlein and Rozengurt, 1996), although in the latter, MAPK/ ERK pathway activation can also occur independently of PKC (Wittau et al, 2000). GAL 2 predominantly couples to a G q/11 -type G protein, leading to phospholipase C activation, which stimulates Ca 2+ release via inositol phosphate hydrolysis and opens Ca 2+ -dependent ion channels in a PTXresistant manner, in both GAL 2 -transfected cell lines (Smith et al, 1997b;Borowsky et al, 1998;Fathi et al, 1998;Pang et al, 1998;Wang et al, 1998c) and GAL 2 -expressing rat microglial cells (Ifuku et al, 2011). GAL 2 activation led to a decrease in both Rho and Cdc42 GTPase activity and activation of cofilin in rat PC12 pheochromocytoma cells (Hobson et al, 2013).…”
Section: B Galanin Receptor Signalingmentioning
confidence: 97%
“…Similarly, intracerebroventricular injection of GALP into Sprague-Dawley rats stimulated production of IL-1a and IL-1b in macrophages and/or microglia in some brain areas (Man and Lawrence, 2008). The BV2 mouse microglia cell line and cultured rat microglial cells solely express GAL 2 (Su et al, 2003;Ifuku et al, 2011), which mediates galanin-induced cell migration and upregulation of class II major histocompatibility complex expression in these innate immune brain cells (Ifuku et al, 2011). Microglial cells also participate in the events leading to multiple sclerosis (Weissert, 2013), and a recent study detected a marked upregulation of galanin expression in microglia associated with multiple sclerosis lesions in postmortem brain tissue from chronic multiple sclerosis patients (Wraith et al, 2009).…”
Section: Galanin Family Peptides and Receptorsmentioning
confidence: 99%
“…Recently it has been shown that GAL is able to influence immune cell behavior by modulating cytokine expression and release, as demonstrated in human neutrophils, natural killer cells, monocytes and macrophages (7,48,54,55). Furthermore, galanin down-regulates microglial tumor necrosis factor-alpha production and induces microglial migration (56,57). Thus, strategies targeting tumor-supportive myeloid cells represent an encouraging novel therapeutic approach and could also be considered for the GAL system.…”
Section: (Supplementarymentioning
confidence: 99%
“…Galanin (GAL) receptor subtypes, designated as GalR1, GalR2, and GalR3, among which GalR2 is reported to be expressed in rat cultured microglia (Su et al, ), activate PKC‐, PI 3 K‐, and Ca 2+ ‐dependent K + channels. GAL downregulates production of TNF‐α (Su et al, ) and induces microglial migration and upregulation of class II major histocompatibility complex expression in microglial cells (Ifuku et al, ). Complementary receptors are present in mouse cultured microglial cells, and application of complement factors (C5a and C3a) induces [Ca 2+ ] response in in situ and in cultured microglial cells by Ca 2+ release from internal pools and subsequent activation of Ca 2+ entry controlled by the filling state of the intracellular stores (Möller et al, ).…”
Section: Ca2+ Responses To Transmitters and Other Signaling Moleculesmentioning
confidence: 99%